Revisiting Enzyme Replacement Therapy for Aspartylglucosaminuria: Truncated Phosphotransferase Enhances Mannose‐6‐Phosphorylation and Cellular Uptake of Aspartylglucosaminidase - Antje Banning; Lidia Reznikova; Adla Murad; Ritva Tikkanen (Journal of Inherited Metabolic Disease, 2026)
ABSTRACT Aspartylglucosaminuria (AGU) is a lysosomal storage disorder caused by a deficiency of aspartylglucosaminidase (AGA), a hydrolase involved in the degradation of N‐glycosylated proteins. Currently, no approved therapies are available for AGU. Development of enzyme replacement therapy (ERT) for AGU has been hampered by the complex proteolytic processing and activation of the AGA enzyme that involves dimerization and cleavage into two subunits. Targeting of AGA into lysosomes is mainly accomplished by a mannose‐6‐phosphate receptor‐mediated pathway, and both AGA subunits contain phosphorylated N‐glycans. In this study, we have developed an overexpression system for an optimized human AGA enzyme and a truncated GlcNAc‐1‐phosphotransferase, S1S3, that is required for the mannose‐6‐phosphorylation. We here show that the Man‐6‐phosphorylation and cellular uptake of AGA are enhanced by the coexpression of S1S3, and high amounts of affinity‐tagged recombinant human AGA can be expressed in HEK293T cells and purified from the culture medium. Impairment of the N‐glycosylation of AGA results in poor uptake into cells, indicating that the Man‐6‐dependent route is the main endocytic pathway of AGA. Furthermore, for optimal uptake, both subunits of AGA need to be glycosylated and Man‐6‐phosphorylated. The results of this study enhance the understanding of the lysosomal targeting mechanisms of AGA and pave the way for the development of ERT for AGU.